Pelatihan Teknologi Drone untuk Pemetaan Pertanian Berkelanjutan Kelompok Tani Kemiri Santoso Desa Kalibaru Manis - Arief, M. Habibullah; Segara, Akbar Pandu; Kartiko, Erik Yohan; Maududie, Achmad; Auliya, Yudha Alif; El Maidah, Nova; Swasono, Dwiretno Istiyadi (Abdimas Indonesian Journal, 2024)
This community service program aims to overcome the low efficiency of agricultural land management in Kalibaru Manis Village, Banyuwangi, by focusing on increasing farmers' knowledge in utilizing drone technology for mapping. This training provides theory and practice of drone operation and processing aerial image data using Geographic Information System (GIS) software. The implementation method includes preparation, training, and evaluation stages. Participants were trained to operate drones, retrieve image data, and analyze it to produce land maps. A collaborative approach between lecturers, students, and practitioners was applied to ensure the success of the program. As a result, participants are able to use drones independently and utilize the data for more effective land management. This program increases agricultural productivity and supports environmental sustainability through the application of modern technology.